Executive functioning in children with ASD + ADHD and ASD + ID: A systematic review. (August 2021) - Benallie, Kandice J.; McClain, Maryellen Brunson; Bakner, Kaelah E.; Roanhorse, Tyus; Ha, Jennifer
Highlights: ASD + ADHD and ASD + ID are associated with more severe EF impairments than ASD only. ASD + ADHD is linked to deficits with flexibility, inhibition, and attention. ASD + ID is linked to deficits with planning, flexibility, attention, and regulation. Understanding EF in ASD and co-occurring NDDs can inform assessment and treatment. Performance-based and indirect measures of EF produce incongruent results. Abstract: Executive functions (EF) are skills that impact an individual's ability to flexibly and efficiently problem solve and react to their environment. Children with neurodevelopmental disorders (NDDs), such as autism spectrum disorder (ASD), commonly experience EF deficits. However, it is unclear how a co-occurring diagnosis of attention-deficit/hyperactivity disorder (ADHD) or intellectual disability (ID) impact EF in children with ASD. This study systematically reviewed 26 studies – within 24 journal articles – that examined EF among children with ASD + ADHD and ASD + ID. Results revealed many non-congruent findings regarding EF in children with ASD + ADHD and ASD + ID, including differences across performance-based and indirect measures of EF. Children with ASD + ADHD exhibited unique flexibility and shifting, inhibition, and attention deficits. Among children with ASD + ID, planning and organizing, flexibility and shifting, attention, behavior regulation, and global EF skills significantly differed from comparison groups. Notably, these findings were dependent on assessment type used (performance-based versus indirect). Furthermore, analyses of mean Z-scores suggest that children with ASD + ADHD and ASD + ID exhibited more severe EF impairments than children with ASD. These results may be used to inform assessment practices for differentiating and determining co-occurring diagnoses. Understanding unique EF deficits may also inform the development of targeted treatment and interventions.